Regras monetárias e taxa de câmbio para o regime de meta de inflação brasileiro - Fachim, Ana Paula Soler Moreno (2002)
The objective of this dissertation is to analyze the use of simple restricted and optimum unrestricted monetary rules for the Brazilian economy, with special attention to the impact of the exchange rate in the transmission of monetary policy. The rules were found by a dynamic programming process e compared in terms of their economic efficiency, measured by the reduction of inflation and product variance. These results were used as a benchmark to evaluate the performance of the Brazilian inflationary target regime, since its implementation in July 1999.